No color is my kind : Eldrewey Stearns and the desegregation of Houston - Cole, Thomas R., 1949- (Austin : University of Texas Press, 2021)
"In 1984, Thomas Cole met Eldrewey Stearns in a Galveston psychiatric hospital. Stearns, a fifty-two-year-old Black man, complained that although he felt very important, no one understood him. Over the course of the next decade, Cole and Stearns, in a tumultuous and often painful collaboration, recovered Stearns's life before his slide into mental illness-as a young boy in Galveston and San Augustine and as a civil rights leader and lawyer who sparked Houston's desegregation movement between 1959 and 1963"--
Preface to the revised edition -- Part one. Leader at last. Launching a movement -- Blackout in Houston -- Railroads, baseball, and the color line -- "I was going places" -- Part two. A boy from Galveston and San Augustine. Uphome -- Rabbit returns -- Driving Mr. Gus -- Part three. Wandering and return. "They got me, but they can't forget me": a mad odyssey -- Drew and me: recovering separate selves
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Stearns, Eldrewey; Cole, Thomas R., -- 1949-; Cole, Thomas R., -- 1949-; Stearns, Eldrewey; Civil rights movements -- Texas -- Houston -- History -- 20th century; African American civil rights workers -- Texas -- Houston -- Biography; Civil rights workers -- Texas -- Houston -- Biography; Mentally ill -- Texas -- Houston -- Biography; Houston (Tex.) -- Race relations; Mouvements des droits de l'homme -- Texas -- Houston -- Histoire -- 20e siècle.; Défenseurs des droits de l'homme noirs américains -- Texas -- Houston -- Biographies; Défenseurs des droits de l'homme -- Texas -- Houston -- Biographies; Personnes vivant avec un trouble de santé mentale -- Texas -- Houston -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY / Cultural Heritage; African American civil rights workers; Civil rights movements; Civil rights workers; Mentally ill; Race relations; Texas -- Houston; 1900-1999; Houston, mental illness, desegregation, Texas history, race in America, civil rights movement, civil rights leader, desegregation movement, bipolar disorder, civil rights; Biographies; History